2021
DOI: 10.3746/pnf.2021.26.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Folate in Milk Fermented by Lactic Acid Bacteria from Different Food Sources

Abstract: Folates are essential micronutrients, and folate deficiency still occurs in many countries. Lactic acid bacteria (LAB) are known to be able to synthesize folates during fermentation, but the folate production is strain-dependent and influenced by the fermentation medium, presence of a folate precursor, and fermentation time. This study aimed to screen extracellular folate-producing LAB from local food sources and evaluate the factors influencing their folate biosynthesis during milk fermentation. The selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
0
16
2
Order By: Relevance
“…Pantothenate and biotin metabolic pathway help in the growth of various lactic acid bacteria (Yao et al, 2018). The water-soluble vitamin B group member folate, particularly in the forms of tetrahydrofolate (THF) and methyltetrahydrofolate (MTHF), is crucial for the carbon-1 transfer processes required for the creation of DNA, nucleic acids, amino acids, and other vitamins (Mahara et al, 2021). These metabolic pathways are attributed to microorganisms fermenting the food, lactic acid bacteria have been found to possess the above KEGG 10.3389/fmicb.2023.1158411 metabolic pathways as previously described in the correlation heat map of major lactic acid bacteria species and KEGG pathways (Cui et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Pantothenate and biotin metabolic pathway help in the growth of various lactic acid bacteria (Yao et al, 2018). The water-soluble vitamin B group member folate, particularly in the forms of tetrahydrofolate (THF) and methyltetrahydrofolate (MTHF), is crucial for the carbon-1 transfer processes required for the creation of DNA, nucleic acids, amino acids, and other vitamins (Mahara et al, 2021). These metabolic pathways are attributed to microorganisms fermenting the food, lactic acid bacteria have been found to possess the above KEGG 10.3389/fmicb.2023.1158411 metabolic pathways as previously described in the correlation heat map of major lactic acid bacteria species and KEGG pathways (Cui et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The inoculum of all LAB isolates was prepared according to a previously described method (18). Bacterial cell pellets grown for 24 h in MRSB were washed twice by centrifugation (Refrigerated Centrifuge LRF-B20, Labtron Equipment Ltd., Camberley, UK) at 10,000 g for 5 min at 4 C and finally resuspended in sterile saline solution (0.85 % w/v NaCl; 106404, Merck KGaA, Darmstadt, Germany).…”
Section: Extracellular Folate Production In Folate-free Mediummentioning
confidence: 99%
“…The report also suggested that both specific and non-specific detections were thought to indicate the presence of a gene. Two isolates, JK6, and BG8, are known folate non-producers (18) and did not have a complete set of folate biosynthesis genes, possibly leading to their inability to produce folate. The JK6 isolate lacked the folQ gene, while the BG8 isolate lacked folQ, folP, and folA, as indicated by the absence of the corresponding bands upon gel electrophoresis (Figs.…”
Section: Detection Of Folate Biosynthesis Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrated the need for the inclusion of crickets into the human diet, especially in resource-poor populations [32]. In a study directed at isolating strains of lactobacilli synthesizing the highest folate concentration by milk fermentation, it was found that Lactobacillus fermentum (from kefir granules), Lactobacillus plantarum (from salted mustard), and Lactobacillus rhamnosus (from breast milk) produced the highest concentrations of folic acid in the absence of pre-existing folate in milk [33]. An interventional study conducted in India to estimate the potentiality of tea as a scalable vehicle for fortification with vitamins B9 and B12 successfully showed that the daily consumption of a cup of vitamin-fortified tea for two months could benefit women of reproductive age [34].…”
Section: Sourcesmentioning
confidence: 99%